Paracambi: estudo de caso do processo de reconversão de uma fábrica de tecidos em 'fábrica do conhecimento' - Santos, Joanilda Maria dos (2017)
The present case study aimed to investigate the process of reconversion of the buildings of a textile factory, Brasil Industrial, in the municipality of Paracambi, in an educational environment - the Fábrica do Conhecimento ('Factory of Knowledge'). It describes and analyzes how this change happened, who are the social actors of the process and if there are reflections and actions in the sense of preserving the factory and worker memory of the city of Paracambi; and if the elements of the city's industrial patrimony are being preserved in accordance with the guidelines of the tipping process of the State Institute of Cultural Patrimony (INEPAC). From the theoretical foundation, analysis of the documentation of the process of tipping and reconversion, and the semi-structured interviews with the managers of the institutions that manage the space, we sought to understand how these issues are handled. The results of the study indicate that there is an ignorance of the process of tipping, and consequently, there are no actions for the preservation of the city's factory memory. The lack of communication between the actors of the reconversion, between the municipal public power, that is the manager of the space, and the INEPAC potentiate the problem; there are internal disputes over the spaces and there is no practical action by the institutions in the sense of patrimonialization of the cultural good